Sistema automatizado de monitoreo preventivo de placas de rodaje para generación de alertas en tiempo real - Gamarra Samaniego, Gustavo Adolfo (2020)
To help address this complex problem of citizen security, an analysis has been carried out under an innovative approach, using methodologies that helped us to identify the main points of pain, the causes and their effects, allowing us to identify and propose possible solutions, analyze their feasibility and prioritize their implementation, supported mainly by the use of information technologies for a disruptive solution and with cutting-edge tools. The automated system of preventive monitoring will allow the identification of suspicious vehicles, will follow up through a predictive algorithm to determine the possible routes it will take and will send alerts to the authorities so that they can take the necessary actions, all in real time, but mainly will provide a tool that will integrate all the interested agencies (district and provincial municipalities, regional governments, ministries of the interior and transport, among others).